The Synergistic Effect of Combining Some Antibiotics with Powder of Silver NPs, Copper NPs and Titanium NPs - Raghad N. Shihab1 , Ali M. Al-Dahbi2 , Saif Ali Mohammed Hussein3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Routine antibiotics susceptibility testing still relies on standardized cultivation-based analyses, includingmeasurement of inhibition zones in conventional agar diffusion tests.The sensitivity of the bacterial isolatescausing Clinical isolatest results showed that all the isolates subjected to this study showed varying resistanceto the antibiotics used. The effect of nanoparticles combined with different antibiotics was investigatedagainst multi resistant Clinical isolates bacteria using disk diffusion method. The inhibition zones diameter(mm) around various antibiotic discs (Trimethoprim, sulphamethaxazol, Azithromycin, Aztreonam,Ceftriaxone, Gentamycin, Tetracyclin, Nitrofurantoin) with/without nanopatrticles against isolates weremeasured. The antibacterial activities of some antibiotics have been increased in the presence of nanoparticleagainst all isolates while others showed no effect. The highest antibacterial activities of antibiotics combinedwith nanoparticle were observed against E.coli isolates for Gentamycin, Trimethoprim-sulphamethaxazol,Azithromycin ,Tetracyclin ,Nitrofurantoin. while A. baumanii appeared sensitive to Gentamycin,Trimethoprim sulphamethaxazol and Azithromycin compared with antibiotics alone. K.pneumoniae becamesensitive to Gentamycin, Tetracyclin and P.aeruginosa to Ampicillin,Trimethoprim sulphamethaxazol,Azithromycin and Gentamycin. nanoparticle showed no effect on antibacterial activities of all antibioticsexcept Gentamycin against gram positive bacteria S.aureus.